A Case Study of Peat Ground Improvement by Vacuum Consolidation in Hokkaido, Japan - Hirochika Hayashi; Hijiri Hashimoto (Indonesian Geotechnical Journal, 2023)
This paper presents the field performance of vacuum consolidation method on peat ground and some technical learning from the field trial. Peat is well known to be a soft soil which has particular characteristics, including extremely high compressibility and greatly low undrained shear strength. In case of an embankment building over peat ground, sliding failure and large settlement often occur due to the particular characteristics. For actual construction sites on peat ground, therefore, some kinds of ground improvement methods are commonly used. One of the methods is the vacuum consolidation method which can load vacuum pressure with the soft ground by vacuum pumps and prefabricated vertical drains to accelerate the consolidation and increases the strength of soft ground. Peat ground distributed widely in Hokkaido, the northernmost land of Japan. A full-scale trial construction of vacuum consolidation was conducted in a highway project over peat deposit in Hokkaido of Japan to reveal its performance. Although the undrained shear strength of peat ground at the trial construction site was approximately 10 kN/m2 and extremely low, a 10.7 m high embankment was successfully built in only 45 days. This experimental fact implies that the vacuum consolidation method has extremely high effects in improving the stability of peat ground. Based on a result of the trial construction, it also revealed that the increase of undrained shear strength of the peat ground using vacuum consolidation and the suitable spacing of prefabricated vertical drains for peat ground.